Chimerism, the Microenvironment and Control of Leukemia - Deeg, H. Joachim (Frontiers in Immunology, 2021)
Transplantation of allogeneic hematopoietic cells faces two barriers, failure of engraftment due to a host versus graft reaction, and the attack of donor cells against the patient, the graft versus host (GVH) reaction. This reaction may lead to GVH disease (GVHD) but in patients transplanted for leukemia or other malignant disorders may also convey the benefit of a graft versus leukemia (GVL) effect. The interplay of transplant conditioning with donor and host cells and the environment in the patient is complex. The microbiome, particularly in the intestinal tract, profoundly affects these interactions, directly and via soluble mediators, which also reach other host organs. The microenvironment is further altered by the modifying effect of malignant cells on marrow niches, favoring the propagation of the malignant cells. The development of stable mixed donor/host chimerism has the potential of GVHD prevention without necessarily increasing the risk of relapse. There has been remarkable progress with novel conditioning regimens and selective T-cell manipulation aimed at securing engraftment while preventing GVHD without ablating the GVL effect. Interventions to alter the microenvironment and change the composition of the microbiome and its metabolic products may modify graft/host interactions, thereby further reducing GVHD, enhancing the GVL effect. The result should be improved transplant outcome.